Entering the Union : European Accession and Capacity-Building Priorities - Wilson, John S.; Luo, Xubei; Broadman, Harry G. (World Bank, Washington, DC, 2012)
The authors examine the impact of trade facilitation on bilateral trade flows. They examine trade facilitation and capacity-building priorities in 12 countries in the Europe and Central Asia region-eight of the current members of the European Union: Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia, and three candidate members: Bulgaria, Romania, and Turkey. The results suggest that behind-the-border factors play an important role in determining bilateral trade flows (controlling for the effects of tariffs, development levels, distance, and regional characteristics of exporters and importers, among other factors). The development of new data sets to expand work related to trade facilitation, including strengthening the empirical work explored here, is a key priority without which intelligent policy and priorities cannot be made. The authors' analysis is based on data from the World Economic Forum, Global Competitiveness Report 2001-2002, World Competitiveness Yearbook 2000, and Kaufmann, Kraay, and Zoido-Lobaton (2002). The results indicate that more gains in exports than in imports are expected should the values of three out of the four indicators (port efficiency, regulatory regimes, and information technology infrastructure) of the new and candidate member countries improve halfway to the EU15 average. These countries would expect large trade gains as well as improvements in trade balances as their integration into the EU continues. For example, the greatest absolute trade gains-$49 billion and $62 billion respectively-could be expected if their port efficiency and information technology infrastructure reach half the average level of the EU, and 70 percent of trade gains are associated with export expansion.